A 51 bp indel polymorphism within the PTH1R gene is significantly associated with chicken growth and carcass traits. (13th May 2020) - Ren, T.; Zhang, Z.; Fu, R.; Yang, Y.; Li, W.; Liang, J.; Mo, G.; Luo, W.; Zhang, X.
Summary: Parathyroid hormone ( PTH ) is a crucial regulator of calcium homeostasis and bone remodeling, and the parathyroid hormone 1 receptor ( PTH1R ) belongs to a class II G‐protein‐coupled receptor. PTH activates PTH1R, which mediates catabolic and anabolic processes in the skeleton. However, the functional mechanism of PTH1R has not been thoroughly elucidated in organisms. This study identified a 51 bp indel mutation in the first intron of the PTH1R gene and elucidated the effect of this gene mutation on the growth and carcass traits in chickens. The results indicated that the 51 bp indel was significantly associated with subcutaneous fat thickness, abdominal fat weight, body weight and daily gain over 4–8 weeks. Furthermore, we found that PTH1R gene expression was highest in the kidney and liver tissues, and it showed a trend of decreasing in leg and breast muscle tissues at different embryonic stages. In addition, we examined the expression of the three genotypes of the PTH1R gene in the liver, breast muscle and abdominal fat and found that the II genotype was significantly higher than the DD and ID genotypes. In summary, these findings suggest that the PTH1R gene can serve as a potential molecular marker for chicken breeding.